Theoretical study of gallium nitride nanocage as a carrier for Cisplatin anticancer drug - Merve Şenğül ALPATER; Zaid H. AL-SAWAFF; Fatma KANDEMİRLİ (GSC Online Press, 2021)
In this paper, the possible interactions between cisplatin Cl2H6N2Pt as an anticancer drug and gallium nitride (Ga12N12) nanocage have been investigated using the DFT/b3lyp/lanl2dz(d,p) level of theory. Three different orientations were used to mimic the cisplatin adsorbed on Ga12N12. To investigate the interaction mechanism between the two components, the adsorption energies and thermodynamic parameters, the electronic properties such as the energies and orbitals distribution of the highest occupied molecular orbital (HOMO), the lowest unoccupied molecular orbital (LUMO), the HOMO-LUMO energy gaps (Eg), thermodynamic properties were also investigated. Additionally, some quantum molecular descriptors were calculated to understand molecular reactivity. The main results revealed that the adsorption process of the drug compound on the surface of the nanocage varies with the adsorption site. The process showed that different energies could be obtained, where the highest energy value was when the drug compound was adsorbed with the nanocage at the chlorine atom, with a value of (41.85) kcal/mol. On the other hand, the distance between the drug compound atoms was affected before and after adsorption, which proves the existence of an interaction between the drug compound and the nanocage and considers it as a drug delivery vehicle.
Keywords: 3. Good health